Evidence of maternal effect on germination and vigor of sour passion fruit - Luciana Domiciano Silva Rosado; João Paulo Gava Cremasco; Carlos Eduardo Magalhães dos Santos; Claudio Horst Bruckner; Maria Helena Menezes Cordeiro; Leandro Luiz Borges (Revista Brasileira de Fruticultura, 2020)
Abstract The seminiferous propagation of Sour Passion Fruit (Passiflora edulis Sims) is the main kind of multiplication due to the ease formation of seedlings. However, the reduced number of productive and homogeneous cultivars reflects the need for genetic breeding. The objective of this study was to assess the maternal and reciprocal effects in vigor and germination of Sour Passion Fruit seeds. The experiment was conducted in a completely randomized design in the factorial scheme, with two structure (hybrid and reciprocal) and ten crosses with four replicates (50 seeds) in trays containing inert sand in germination chamber. Before sowing, it was obtained the weight of 100 seeds, and at 28 days germination percentage, emergence speed index, total seedlings length, shoot length and main root length, number of normal seedlings and dry mass per seedlings were evaluated. The reciprocal effects tell us which genotype is most promising when used as the female or male parent for the trait studied. It can be inferred that there is maternal effect influencing the weight of 100 seeds, emergence, emergence speed index and the number of normal seedlings. There was influence of the parent on the expression of traits in seeds of Sour Passion Fruit. It is important to define the paternal and maternal parent to obtain seeds with high germination potential.